(untitled) (Research, Society and Development, 2024)
To present the risks and adverse effects caused by the irrational use of medications in the treatment of insomnia among young people. This is a systematic literature review, based on studies on self-medication in young people with insomnia, focusing on the adverse factors described in these studies. This search was carried out in scientific databases, such as Google Scholar, PubMed, Scielo, Science Direct and USP Theses. Of the total number of articles found, which analyze drugs used for the treatment of insomnia, 18 were selected to compose this systematic literature review. The study concludes that young people irrationally use medications to treat insomnia for several factors, the most used medications according to the literature are benzodiazepines, such as Clonazepam, melatonin and Z Hypnotics, such as Zolpidem. The indiscriminate use of these drugs in the fight against insomnia causes adverse effects and health risks to young people, who should seek specialized treatment to treat the problem effectively and safely.